Efeito agudo de um protocolo específico de potencialização pós-ativação sobre o desempenho na saída de bloco de nadadores competitivos - Luiza Ferreira Vieira (2017)
Performance during the start is determining of overall success in competitive swimming, specially in short-distance events. Preparatory muscle activities prior to the aimed sports action are believed to enhance performance (PAP), and various mechanisms have been proposed to explain this. Furthermore, it is suggested that the specificity of muscle action in the exercise protocol conceived to trigger a PAP may be of relevance. The main aim of the present investigationis to test the effectivity of 2 preparatoryprotocols (a specific and a non-specific protocol) designed to achieve a PAP on enhancing swimming overall start performance. The sample was composed by 12national level swimmers (age 20,8 ± 3,0 years; height 173,1 ± 6,79 cm; weight 66,5 ± 5,53 kg). They carried out 3 maximal 50 meter crawl sprints in different days, prior to which they underwent 3 different preparatory exercise protocols: a control situation with no prior exercise (Control); a non-specific protocol consistedof 3 sets of isometric squats (convencional PAP) and a specific protocol, in which subjects performed 3 sets of maximal isometric contractions in the start position (attached to a wooden start block) (SpecificPAP). The test conditions were randomized. Time to 15 meters swimming, time to swim 50 meters, reaction time, horizontal start velocity, horizontal and vertical peak power, horizontal and vertical impulse, horizontal and vertical peak of force development were recorded. No significant differences were observed in all the variables between situations, except the 15m swimming times. After performing the specific preparatory exercises, 15m swimming times were significantly shorter when compared to Control (p<0.05) (Control: 7,221 ± 0,411s;Specific 7,148 ± 0,442s). Shorter swimming times (15 meters) were observed after the specific preparatory exercise protocol, even though the othersvariables showed no alterations. The underwater phase is expected to influence performance 15m swimming times, although it is not possible, in the light of the data obtained, to identify with accuracy which variables determined the best performance